2020
DOI: 10.21043/bisnis.v8i1.7045
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Gaya Kepemimpinan Transformasional dan Tranksaksional Terhadap Kinerja Sistem Jaminan Halal HAS 23000

Abstract: This study aims to analysis of transformational and transactional leadership styles and their effects on the performance of the HAS 23000 Halal Assurance System implementation in the food industry in Tangerang. The respondents of the study was employees in several food industries that were located in the Tangerang  who had implement the HAS 23000 Halal Assurance System as many as 200 employees and data collection methods by giving online electronic questionnaires to 2000  employees randomly. The analytical too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
9

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 2 publications
0
7
0
9
Order By: Relevance
“…Therefore, paying attention to the leadership practices in every unit of society, especially in business organi-zation is very important and crucial Asbari et al, 2020;Fikri et al, 2020;Sopa et al, 2020aSopa et al, , 2020b. However, in the research field was found that transformational leadership practice does not give significant influence to the performance of employees (Asbari, 2019;Fayzhall et al, 2020;Jumiran et al, 2020;Maesaroh et al, 2020;Nugroho et al, 2020;Waruwu et al, 2020;Yanthy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, paying attention to the leadership practices in every unit of society, especially in business organi-zation is very important and crucial Asbari et al, 2020;Fikri et al, 2020;Sopa et al, 2020aSopa et al, , 2020b. However, in the research field was found that transformational leadership practice does not give significant influence to the performance of employees (Asbari, 2019;Fayzhall et al, 2020;Jumiran et al, 2020;Maesaroh et al, 2020;Nugroho et al, 2020;Waruwu et al, 2020;Yanthy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Oleh karena itu, memperhatikan praktek kepemimpinan pada setiap unit sosial masyarakat, apalagi pada organsiasi bisnis menjadi penting dan genting Fikri et al, 2020;Sopa et al, 2020aSopa et al, , 2020b.Walaupun demikian, di lapangan penelitian ditemukan bahwa praktek kepemimpinan transformasional tidak memberikan pengaruh signifikan terhadap kinerja karyawan, sebagaimana beberapa penelitian berikut ini: (David et al, 2017;Eliyana et al, 2019;Khalifa Elgelal & Noermijati, 2014;Makena, 2017;Putri & Soedarsono, 2017;Siswatiningsih et al, 2019). Berbeda dengan beberapa penelitian mapan lainnya yang menyebutkan bahwa kepemimpinan transformasional berpengaruh signifikan terhadap kinerja karyawan (Asbari, 2019;Jumiran et al, 2020;Maesaroh et al, 2020;Nugroho et al, 2020;Waruwu et al, 2020;Yanthy et al, 2020). Sehubungan masih ada terjadi research gap di dalam hubungan antara kepemimpinan transformasional, kesiapan untuk berubah dan kinerja karyawan, maka penelitian ini dipandang perlu untuk dilakukan.…”
unclassified
“…Walaupun demikian, di lapangan riset ditemukan bahwa praktik kepemimpinan transformational tidak memberikan pengaruh signifikan terhadap kinerja pegawai, sebagaimana beberapa riset berikut ini: (David et al, 2017;Eliyana et al, 2019;Khalifa Elgelal & Noermijati, 2014;Makena, 2017;Monoyasa et al, 2017;Putri & Soedarsono, 2017;Siswatiningsih et al, 2019). Berbeda dengan beberapa riset mapan lainnya yang menyebutkan bahwa kepemimpinan transformational berpengaruh signifikan terhadap kinerja pegawai Jumiran et al, 2020;Nugroho et al, 2020;Waruwu et al, 2020;Yanthy et al, 2020). Serelasi masih ada terjadi research gap di dalam relasi antara kepemimpinan transformational, mentalitas siap berubah dan kinerja pegawai, maka riset ini dipandang perlu guna dilakukan.…”
Section: Pendahuluanunclassified